Keterlibatan Pemangku Kepentingan dalam Laporan Keberlanjutan PT Pertamina Berbasis GRI Standar 2021 - Veren Putri Shamaya; Alhabsyi, Amru; Maria Yovita R Pandin (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This study aims to analyze stakeholder engagement in the preparation of PT Pertamina's sustainability report based on the GRI 2021 standards. The method used is descriptive qualitative research utilizing secondary data from PT Pertamina's 2023 sustainability report, analyzed based on GRI 2-29 disclosure. The results show that PT Pertamina involves various stakeholders, including shareholders, customers, employees, regulators, and communities, through active dialogue, routine reporting, surveys, and specific programs. This engagement enhances transparency, credibility, and sustainability performance while building public trust and minimizing operational risks. This study is limited to data from 2023 and does not include direct interviews with stakeholders, which restricts a comprehensive representation of their perspectives. Future research is recommended to analyze data over multiple years, include direct stakeholder interviews, and explore other reporting frameworks to broaden insights and provide more comprehensive recommendations